The Influence of Financial Reporting Quality on Performance of listed companies in Vietnam - An, Ha Anh (2022)
This research project examines the influence of financial reporting quality (FRQ) on performance of listed companies in Vietnam. For this purpose, I use panel data sample including 722 firms on Vietnam stock market (HNX and HOSE) over the period of 2014-2020 and apply fixed effects regression model to find the relation between three proxies of FRQ: (1) discretional accruals adjustment, (2) accruals quality and (3) degree of accounting conservatism and two indicators of performance: ROA and ROE. The results show that firms with good financial reporting quality enjoy better performance. Therefore, listed companies in Vietnam can pay more attention to enhance their FRQ and accounting environment. Further, when taking interaction of FRQ and IFRS adoption and Big 4 audit service into account, I found not enough evidence to draw a conclusion about impact of them on FRQ-performance relation. However, the case of IFRS adoption is due to insignificant results while Big 4 audit service has inconsistent interactions with each FRQ proxy.